Effect of Rice Straw, Pseudomonas fluorescens, and Azotobacter sp. on Soybean Growth and Productivity in Calcareous Soil - Kurniawati, Yusfita; Rahayu, Yuni Sri (LenteraBio : Berkala Ilmiah Biologi, 2022)
This study aimed to determine the effect of rice straw, P. fluorescens, and Azotobacter sp. on nutrient levels, soybean growth and productivity in calcareous soil. Randomized Block Design was used with combination of rice straw; P. fluorescens, Azotobacter sp., rice straw + P. fluorescens, rice straw + Azotobacter sp., rice straw + P. fluorescens + Azotobacter sp. with 3 repetitions. Parameters included are levels of N and P, growth parameters (amount of root nodules, active root nodules, biomass of root nodules, plant height, leaf amount, root length & plant biomass), and productivity parameters (amount and biomass of pods). The result were analyzed descriptively quantitatively using one-way ANOVA followed by Duncan's test. The results showed that combination of rice straw, P. fluorescens & Azotobacter sp. has significant differences in Phospor levels, root nodule biomass, plant height, leaf amount and plant biomass. Azotobacter sp. has the best result on Nitrogen levels. P. fluorescens has the best result on P levels, root length, amount and active root nodules. Nevertheless, rice straw and Azotobacter sp. has the best result on growth parameters (root nodule biomass, plant height; leaf amount & plant biomass) and productivity parameters (amount and biomass of pods).